PENGARUH PERSEPSI DUKUNGAN ORGANISASIONAL TERHADAP KOMITMEN AFEKTIF DENGAN KEPUASAN KERJA SEBAGAI PEMEDIASI PADA PT. TELKOM INDONESIA TBK PUSAT TERNATE - Salim, Sunarti; Sabuhari, Rahmat (Jurnal MS, 2022)
The purpose of this study was to determine and analyze: (1) the positive and significant effect of perceived organizational support on affective commitment; (2) the effect of perceived organizational support positively and significantly on job satisfaction; (3) The effect of job satisfaction positively and significantly on Affective Commitment; and (4) Perception of Organizational Support positively and significantly towards Affective Commitment through job satisfaction at PT Telkom Indonesia, Ternate City.The data analysis technique used in this study is SEM analysis using Smart Partial Least Square (PLS) version 3 as a statistical test tool. Methodology: The analytical model used are Structural Equation Modeling with SMART PLS as tools for the statistical test. Data collection tools used are questionnaires and interviews, and the number of respondents was 151 employee. Finding: The results of the SEM-SMART-PLS calculation show that the t-statistic value of 5.854 is greater than the t-table of 1.96 and the value of = 5% is smaller than the p-value of 0.000. This means that hypothesis 1 is accepted.Furthermore, the second hypothesis testing shows the tstatistic value of 8,047 which is greater than the t table value of = 5%, which is smaller than the p-value of 0.000. Testing the third (H3) hypothesis shows that the t-statistic value of 6.708 is also greater than the t-table value of = 5% smaller than the p-value of 0.000. This means that hypothesis 3 is accepted. Testing the fourth hypothesis (H4), namely the t-statistic value of 4,870, the value of = 5%, which is smaller than the p-value of 0.000. This means that hypothesis 4 is accepted. Conclusion: The conclusions in this study are: (1) Perception of organizational support has a significant positive effect on affective commitment; (2) Perception of organizational support has a significant positive effect on job satisfaction; (3) Job satisfaction has a significant and positive effect on affective commitment; and (4) job satisfaction is a variable mediating the effect of perceived organizational support on affective commitment.